2011
DOI: 10.1128/jcm.02047-10
|View full text |Cite
|
Sign up to set email alerts
|

Clinically Healthy Skin of Dogs Is a Potential Reservoir for Canine Papillomaviruses

Abstract: Papillomaviruses have been linked to several skin disorders in the dog. In order to have a suitable diagnostic tool for canine papillomavirus detection, eight PCRs with published primer combinations were evaluated. The most sensitive PCR was used to demonstrate that papillomavirus DNA can be detected on nonlesional skin of dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
68
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 23 publications
0
68
2
Order By: Relevance
“…Furthermore, an OSCC developed in an area of papillomatosis (Watrach et al, 1970) and CPV-1 DNA was detected using specific PCR primers in 3/29 canine OSCCs (Teifke et al, 1998). However, despite both the CP4/5 and the FAP59/64 primers being highly sensitive for CPV-1 (Lange et al, 2011), CPV-1 was not detected in any OSCC in the present study. Similarly CPV-1 DNA was not detected in a previous study of 21 canine OSCCs (Zaugg et al, 2005) suggesting that CPV-1 is rarely associated with these neoplasms.…”
contrasting
confidence: 79%
“…Furthermore, an OSCC developed in an area of papillomatosis (Watrach et al, 1970) and CPV-1 DNA was detected using specific PCR primers in 3/29 canine OSCCs (Teifke et al, 1998). However, despite both the CP4/5 and the FAP59/64 primers being highly sensitive for CPV-1 (Lange et al, 2011), CPV-1 was not detected in any OSCC in the present study. Similarly CPV-1 DNA was not detected in a previous study of 21 canine OSCCs (Zaugg et al, 2005) suggesting that CPV-1 is rarely associated with these neoplasms.…”
contrasting
confidence: 79%
“…Bovine papillomaviruses are not unique in this regard; in fact, papillomaviruses are commonly found on healthy skin of humans and animals. [3][4][5]15,20 Therefore, prudence is required when interpreting the presence of amplified papillomavirus DNA. Among PCR-based equine studies, reported prevalence of BPV amplified from nonsarcoid (normal or inflamed) tissues ranges from 0% to 80%.…”
Section: Discussionmentioning
confidence: 99%
“…These viral papillomas are more common in older, immunosuppressed patients and are associated with particularly malignant lesions in a group of dogs with X-linked severe combined immunodeficiency (Goldschmidt et al, 2006). Normal skin may harbor CPVs, but often these infections remain subclinical in immunocompetent hosts (Lange et al, 2011). It remains unknown, however, if or how the immune system specifically recognizes PV infections and induces an effective antiviral immune response.…”
Section: Introductionmentioning
confidence: 99%